Implementation of Biological Asset Accounting Treatment Based on PSAK No. 69 Effective January 1, 2018 at HT Coffee - Abdallah, Zachari; Kurniawan , Irgi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
PSAK 69 regulates the accounting treatment and disclosure of agricultural activities that are the harvest of biological assets owned by the entity, at the harvest point. This study aims to find out how the accounting treatment of biological assets in terms of recognition, measurement, and disclosure in the company's financial statements and aims to find out the comparison of the treatment of biological assets applied by the company with the accounting treatment of biological assets based on PSAK 69 AgricultureThe research method used in this study is qualitative descriptive. The data sources used are primary data and secondary data in the form of financial statements and records regarding the recognition, measurement and disclosure of biological assets. The data collection techniques used include observation, documentation, and interviews on HT Coffee has used PSAK 69 as the standard for the accounting treatment of biological assets. Starting from bending, measurement, to reporting has been in accordance with PSAK 69. except for the depreciation of biological assets or depreciation of plants and machinery that have been able to provide benefits to the company such as agricultural products.